THE STRUCTURE OF MYTH FOUND IN PRAMOEDYA'S THE KING, THE WITCH AND THE PRIEST - Deta Maria Sri Darta (Celt: A Journal of Culture, English Language Teaching & Literature, 2011)
Being a part of a certain culture makes a literary work is not immune from its influence. This applies also to literary works which deliver stories from the past, Pramoedya Ananta Toer's The King, The Witch and The Priest for example. To confirm the influence, this article would like to see the structure of myth in this story with the help of Greimas' Actantial Model. Under the approach of structuralism, finding the six actants of some important actions selected from the plot analysis is conducted to discover the pattern. The pattern then is used to understand the structure of mythfound in the story. This study results on the existence of the structure of myth whereby the good one always wins at the end of the story, no matter how powerful the evil is.